2017
DOI: 10.1111/exd.13467
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐17 alters the biology of many cell types involved in the genesis of psoriasis, systemic inflammation and associated comorbidities

Abstract: Psoriasis is a chronic, immune-mediated, systemic inflammatory disease that is defined by a characteristic skin reaction produced when elevated levels of inflammatory cytokines such as interleukin (IL)-17 alter the growth and differentiation of skin cells.The pathogenesis of comorbid conditions associated with psoriasis, including psoriatic arthritis, cardiovascular disease, obesity, metabolic syndrome, liver disorders, renal disease and depression, is also largely affected by inflammation. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 122 publications
2
90
0
3
Order By: Relevance
“…An American study of 1776 patients with HS found that 57% of patients had at least one psychiatric disorder, thus making psychiatric disorders one of the most common comorbidities in patients with HS . Elevated levels of interleukin 17 (IL‐17) have been found in both depression and anxiety . Schlapbach et al .…”
Section: Discussionmentioning
confidence: 99%
“…An American study of 1776 patients with HS found that 57% of patients had at least one psychiatric disorder, thus making psychiatric disorders one of the most common comorbidities in patients with HS . Elevated levels of interleukin 17 (IL‐17) have been found in both depression and anxiety . Schlapbach et al .…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is associated with a range of inflammatory and metabolic comorbidities, including obesity, diabetes, dyslipidemia, hyperuricemia and psychiatric conditions, and is associated with increased cardiovascular risk . The exact aetiology of comorbidity in psoriasis remains a topic of current research, but a state of systemic low‐grade inflammation induced by dysregulated Th1 and Th17 activation may contribute to the development of (pre)diabetes, obesity, non‐alcoholic fatty liver disease (NAFLD) and atherosclerosis …”
Section: Introductionmentioning
confidence: 99%
“…However, several population‐based studies primarily based on Western populations revealed that psoriasis is an independent risk factor for an increased incidence of MI and ischemic events after adjusting cardiovascular risk factors . Highly increased levels of pro‐inflammatory molecules and cytokine‐activated leukocytes entering systemic circulation have been implicated in the resultant cardiovascular and metabolic comorbidities in psoriatic individuals . Indeed, certain transgenic mouse models of psoriatic inflammation were shown to be prone to developing thrombotic comorbidity which was protected by inhibition of IL‐23 or IL‐17A .…”
Section: Discussionmentioning
confidence: 99%